2011
DOI: 10.1021/jf200968x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glutathione on the Formation of Methylmethine- and Carboxymethine-Bridged (+)-Catechin Dimers in a Model Wine System

Abstract: This study was performed to assess the impact of glutathione on the reaction between (+)-catechin and carbonyl compounds in wine-related conditions. (+)-Catechin (0.50 mM) and either glyoxylic acid (0.25 mM) or acetaldehyde (0.25 mM) were added to a model wine system with 0.0, 0.25, and 2.5 mM of glutathione added. UPLC-DAD and LC-MS analysis showed that the formation of carbonyl-bridged (+)-catechin dimers was inhibited in the samples with a glutathione to carbonyl ratio of 10:1 compared to the samples withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…In the pH range 2-6, lower pH values increase the rate of reaction for SO 2 (Drexler et al 1991), while the oxidation rate of GSH by hydrogen peroxide increases with increasing pH (Finley et al 1981). However, taking into account the low amount of GSH used in this experiment and the high O 2 :GSH molar reaction ratio, it seems that the more relevant effect produced by GSH is due to other reactions than to its reaction with H 2 O 2 , likely due to its capability of reacting rapidly with quinones (Nikolantonaki and Waterhouse 2012) and other organic compounds such as catechin, hydroxycinnamic acids, and carbonyls involved in wine oxidation (Bouzanquet et al 2012, Sonni et al 2011b). …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the pH range 2-6, lower pH values increase the rate of reaction for SO 2 (Drexler et al 1991), while the oxidation rate of GSH by hydrogen peroxide increases with increasing pH (Finley et al 1981). However, taking into account the low amount of GSH used in this experiment and the high O 2 :GSH molar reaction ratio, it seems that the more relevant effect produced by GSH is due to other reactions than to its reaction with H 2 O 2 , likely due to its capability of reacting rapidly with quinones (Nikolantonaki and Waterhouse 2012) and other organic compounds such as catechin, hydroxycinnamic acids, and carbonyls involved in wine oxidation (Bouzanquet et al 2012, Sonni et al 2011b). …”
Section: Resultsmentioning
confidence: 84%
“…However, this is the first observation that GSH can inhibit acetaldehyde production in wine oxidation during MOx. It is known that GSH binds acetaldehyde (Sonni et al 2011b) and that oxidation of GSH yields several oxidation products when it reacts with hydrogen peroxide in aqueous solution at pH values close to that of wine (Finley et al 1981). Thus, it seems possible that this molecule exerts a protective function in wine by several possible mechanisms: (i) scavenging hydrogen peroxide, (ii) by direct reaction with wine phenolics (Bouzanquet et al 2012, Sonni et al 2011a by way of quinones (Nikolantonaki and Waterhouse 2012), and (iii) binding acetaldehyde to a less extent with respect to SO 2 (Sonni et al 2011b).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the formation of larger amounts of glyoxylic acid showed that SO 2 was not able to completely prevent the first oxidation step of tartaric acid. However its ability to react with oxidation products inhibits the further reactions involved in xanthylium cation formation probably generating a bisulfite addition product with glyoxylic acid [4]. Regarding the effect of AA addition, there seems to be a competitive effect with the xanthylium cation formation.…”
Section: Influence Of So 2 Aa and Gsh On Xanthylium Cation Formationmentioning
confidence: 99%
“…The antioxidative effect of SO 2 is based on the direct reaction with H 2 O 2 as high amounts of SO 4 2-could be detected. Furthermore, the formation of larger amounts of glyoxylic acid showed that SO 2 was not able to completely prevent the first oxidation step of tartaric acid.…”
Section: Influence Of So 2 Aa and Gsh On Xanthylium Cation Formationmentioning
confidence: 99%
See 1 more Smart Citation